Pengaruh Substitusi Parsial Pasir Silika Sebagai Agregat Halus Terhadap Karakteristik Campuran Aspal AC-WC Berdasarkan Metode Marshall - Subhan Mulyana; Athaya Zhafirah; Ari Fajar Gumilar (Jurnal Konstruksi, 2026)
The development of transportation infrastructure in Indonesia has increased the demand for high-quality pavement materials, particularly for the wearing course or Asphalt Concrete–Wearing Course (AC-WC), which functions as the top layer and directly receives traffic loads. One of the key factors determining pavement quality is fine aggregate. To date, fine aggregates are predominantly sourced from natural sand; however, its availability is limited and its quality is not always consistent. Therefore, alternative materials are needed to improve asphalt mixture performance. Silica sand, with its high SiO2 content, rough texture, and good hardness, has potential as a substitute for fine aggregate. The novelty of this study lies in a comprehensive evaluation of silica sand substitution variations (0%, 25%, 50%, and 75%) on the Marshall parameters of AC-WC to determine the optimum content that provides the best performance. The substitution limit of 75% was set based on economic considerations, as silica sand is more expensive than natural sand. Experimental laboratory testing was conducted in accordance with the 2018 Bina Marga General Specifications, with parameters including stability, flow, Void in Mixture (VIM), Void in Mineral Aggregate (VMA), Void Filled with Bitumen (VFB), and Marshall Quotient (MQ). The results indicate that the use of 25% and 50% silica sand increases stability while still meeting all Marshall parameters specified. However, at 75% substitution, although stability increases, the VIM and VMA values do not meet the required standards. From a durability perspective, the 25%–50% variations result in a stiffer mixture with potential cracking risk. Therefore, the optimum silica sand substitution content is in the range of 25%-50% for improving stability, although further evaluation of durability is required.